Characteristics of Oak (Quercus petraea (Matt.) Liebl), hornbeam (Carpinus betulus L.) and ash (Fraxinus excelsior L.) in a plain-low hills-mountains-plateau sequence - Crișan Vlad Emil; Dincă Lucian; Vasile Diana; Murariu Gabriel; Drasovean Romana; Mocanu George Dănuț; Georgescu Lucian; Apăfăian Andrei (Heliyon)
The climate has changed significantly over the past few decades around the globe. To make meaningful comparisons between changes occurring over time in the tree world, comprehensive databases on the most important species and their evolution must be created. It is essential to consider latitude, longitude, altitude and local relief when analyzing data. Given the extensive distribution of oak, hornbeam and ash, a sequence analysis was conducted to definitively examine the characteristics of these species in West Plain, West Hills, Apuseni Mountains and Transylvania's Tableland. The data for all the regions comprised a total of 708511 ha, which were subjected to rigorous analysis to determine characteristics such as yield class, volume, increment, structure and participation percentage. The data was analyzed using the most appropriate modern statistical programs, including correlation matrices, ANOVA, principal component analysis, matrix data analysis and the cluster method. In relation to the altitudinal variation, oak is present at average altitudes of 200–250 m in West Plain, 400–500 m in West Hills and Transylvania's Tableland, and 900–950 m in Apuseni Mountains. Hornbeam has a similar spreading with oak, but records its presence in slightly higher altitudes of West Hills (400–700 m) and lower in Apuseni Mountains (700–750 m). Volume is also an important indicator, as it is susceptible to climate change. Oak has the highest age-volume, over 95 years, while ash and hornbeam have it less than 90 years. The results are crucial for understanding the ecological requirements of oak, hornbeam and ash, as well as for effectively managing these forests.